Kant and the law of war - Ripstein, Arthur (New York, NY : Oxford University Press, 2021)
An intervention into just war theory by the most influential contemporary interpreter and exponent of Kant's legal and political philosophy. Building on Kantian foundations, it offers a reconceptualization of the duties of the state and the norms governing war. Ripstein argues that a special morality governs war because of its distinctive immorality: The wrongfulness of entering or remaining in a condition in which force decides everything provides the standards for evaluating the grounds of initiating war, the ways in which wars may be fought, and the results of past wars.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 10, 2021).
Keywords: War -- Moral and ethical aspects; War (Philosophy); Kant, Immanuel, -- 1724-1804.